Nitrogen input enhances the impacts of emigration and immigration on plant species composition in a temperate grassland - Zhengru Ren; Yuqiu Zhang; Haining Lu; Xu Chen; Ruoxuan Liu; Jungang Chen; Yunhai Zhang (Ecosphere)
Abstract Human‐induced increase in atmospheric nitrogen (N) deposition has decreased species diversity at the local scale (α diversity) over global grasslands. However, whether and how biodiversity at the larger spatial scale (γ diversity) responds to N deposition remains an open question. As γ diversity is affected by both α diversity and β diversity (i.e., diversity among localities), it is important to explore the spatiotemporal response of β diversity under N enrichment. A field N addition (10 g N m−2 year−1) experiment was conducted from 2014 in an Inner Mongolian grassland, China. A metacommunity consisting of four permanent 1 m × 1 m quadrats (local communities) within each experimental plot was established. Thus, there were eight metacommunities for each treatment. By collecting plant species richness and composition over the first six consecutive years (2015–2020), we found that N addition decreased α and γ diversity, but did not alter β diversity at the community level and its temporal change (Δβ diversity) at the species level. Nitrogen addition increased the magnitudes of species temporal migration (both emigration and immigration) on Δβ diversity at the species level. But N addition did not change the role of species relative coverage on the relationship between species temporal migration and Δβ diversity at the species level. Therefore, our study suggests that species temporal gain and loss do play important roles in shaping community assembly under N addition in the temperate grassland.